Secretome improves testosterone and androgen-binding protein production in testicular dysfunction rats induced by cisplatin (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: This study was determined to see the effects of secretome on cellular production of testosterone and androgen-binding protein (ABP) using immunohistochemistry in testicle dysfunction due to cisplatin.  Materials and Methods: Forty-eight rats were divided into four groups: the healthy group, the group with testicular dysfunction, the secretome-treated group with 0.2 ml/kg body weight (BW), and the secretome-treated group with 0.3 ml/kg BW. The immunohistochemistry staining method is used to find out testosterone and ABP reactivity in tissue organs.  Results: Very strong testosterone and ABP immunoreactivity were found in Leydig cells of normal testes. While in the Leydig cells of cisplatin-induced testicles, testosterone and ABP immunoreactivity were not observed. Testosterone and ABP were observed 1 week after the second secretome injection. The number of testosterone-immunoreactive cells in the low dose group from week 1 to 3 was 0, 19, and 32, respectively. From week 1 until week 4, the high dose group was 0, 29, 33, and 65, respectively. The number of ABP-immunoreactive cells from the first week until the third week in the low dose group was 0, 28, and 34, respectively. The high dose group from the first week until the fourth week was 0, 26, 58, and 83, respectively. The number of cells that produce testosterone and ABP increased from week 2 to 4.  Conclusion: The administration of secretome could increase the number of immunoreactive cells toward testosterone and ABP in testicular dysfunction.J. Adv. Vet. Anim. Res., 8(4): 687–694, December 2021http://doi.org/10.5455/javar.2021.h561